Heat transformation based on CaCl2/H2O – Part B: Open operation principle. (5th June 2016) - Bouché, Martin; Richter, Margarethe; Linder, Marc
Highlights: Thermal upgrade of waste heat using a thermochemical system. Dehydration of calcium chloride dihydrate using air represents charging process. Open operation principle in a fixed bed. Parametric experimental study regarding charging temperature and air flow rate. Thermal charging at 100 °C with long duration of reaction. Abstract: In order to increase the efficiency of industrial processes by means of thermal energy storage and upgrade of waste heat in a temperature range of 100–200 °C thermochemical systems are a promising option. The working pair CaCl2 /H2 O has been identified as suitable reference system due to the possibility to store thermal energy and perform an upgrade of thermal energy at the same time. As working principle an open mode with air as purge gas is investigated in this work. Thus, an operation at ambient pressure level as well as a less complex experimental setup can be realized. Therefore, a test facility has been set up for experimental investigation of the thermochemical system focusing on dehydration reaction. First, various reactor modifications are examined with respect to influence the pressure drop of the reactor containing the CaCl2 . It was shown that by the insertion of gas channels made of fine metal mesh a reduction of the pressure drop by factor 6 is possible in comparison to the unmodified fixed bed. Additionally, parametric studies have been carried out regarding the variation of charging temperature and volume rate of air. In order to obtain a high temperature lift in the heat transformation process, low thermal charging temperatures are targeted.